Correlation between body mass index and waist circumference among diabetes mellitus patients in Denpasar, Bali - Kausalya Neelamagam; Desak Made Wihandani (Intisari Sains Medis, 2018)
Background: Obesity is one of the most important modifiable risk factors for type 2 diabetes. There are two types of obesity the general obesity which measured using the body mass index (BMI) and central obesity measured by using waist circumference (WC) or waist/hip ratio. This research aims to investigate the correlation between body mass index and waist circumference among diabetic patients in Indonesian population.Methods: The study was carried out using the cross-sectional plan, by analyzing the secondary data that was collected from previous research on diabetic patients that was conducted in Medical Faculty of Universitas Udayana, Bali. The research was done in 4 months from October 2015 - January 2016, and the data was categorized based on BMI, WC, gender, age, family history of diabetes and duration of diabetes mellitus.Results: On a total of 96 sample there were 5 (5.2%) were having general obesity BMI >30 kg/m2, while 61(63.5%) were having central obesity, where the WC measurement for a male was >102 cm and for a female was >88 cm. From the study, it proves that there was a strong correlation in between BMI and WC (r = 0.752, ð‘ƒ < 0.01). It indicates the correlation was positive and significant.Conclusions: It is concluded that people who have a higher BMI tend to have a higher waist circumference value and with that, both the BMI and WC strongly correlate. As a suggestion, it is recommended to conduct the study using primary data for future research